UKRAINE-IMF RELATIONS AS AN IMPORTANT FACTOR OF THE NATIONAL ECONOMIC SECURITY - Sharov, Oleksandr (Journal of European Economy, 2018)
The article considers the issues of establishing relations with the International Monetary Fund in the context of the necessity to achieve the goals of national economic security. After analyzing the process of creating the IMF and defining its objectives, as well as the practice of relations between the IMF and member states, in particular with Ukraine, the author has come to several conclusions. In their opinion, Ukraine shouldn’t blindly follow the recommendations of the actually trained experts of this organization, but rather propose effective reform measures that would provide for solving a complex of economic problems. These problems include: a) financial and macroeconomic stabilization (IMF’s formal objectives); b) ensuring the prospects for economic growth (program objectives of the government); and (c) guaranteeing Ukraine’s economic security (constitutional obligation of the President and other bodies of state power). JEL: F02, F33, F52.